Wildlife Communication - Steen, Kim Arild; Therkildsen, Ole Roland; Karstoft, Henrik; Green, Ole (Technical Report Electronics and Computer Engineering, 2012)
This report contains a progress report for the ph.d. project titled “Wildlife Communication”. The project focuses on investigating how signal processing and pattern recognition can be used to improve wildlife management in agriculture. Wildlife management systems used today experience habituation from wild animals which makes them ineffective. An intelligent wildlife management system could monitor its own effectiveness and alter its scaring strategy based on this.